Fabrication and Performance of a Microbial Fuel Cell: Utilization of Modified Nafion Membrane with Carbon Powder as Separator and Bio-Anode - Mustapha Abdeldjabar Charef; Hakima Kebaili; Mostefa Kameche; Christophe Innocent (Indonesian Journal of Chemistry, 2021)
A Microbial Fuel Cell (MFC) was conceived by using garden soil as a source to culture. It was then utilized as a bio-catalyst to decompose waste organic matter, reduce pollution from the soil, and produce energies. The MFC was composed of a bio-anode inoculated with a mixture of garden compost leachate and an abiotic stainless steel cathode. Besides, the bio-anode consisted of a Nafion membrane modified with carbon. The microorganisms agglomerated under polarization and formed electroactive bio-film onto bio-anode. In the preliminary test of MFC, potassium hexacyanoferrate has been utilized as catholyte, to enhance the reduction of proton and electrons resulting in a higher voltage. However, this electrolyte is toxic and oxidized rapidly, thus substituted by the hydrochloric acid. The results showed that the MFC with modified Nafion, gave relatively high current-density 379 mA/m2 in two days, whereas the conventional biofuel cell without modification attained the current-density 292 mA/m2 in four days. Nevertheless, both cells yielded almost the same current density of 20 mA/m2 during 60 days. Although it has been used for a long time, the modified Nafion has not been corroded and preserved its physicochemical properties.